Genetic evaluation of grain sorghum hybrids in Brazilian environments using the REML/BLUP procedure - Janeo Eustáquio de Almeida Filho; Flávio Dessaune Tardin; Marcos Deon Vilela de Resende; Fabyano Fonseca e Silva; Ítalo Stefanine Correia Granato; Cicero Beserra de Menezes (Scientia Agricola, 2014)
When it comes to recommending sorghum (Sorghum bicolor) cultivars, it is essential to carry out a genetic evaluation of the agronomic traits of promising genotypes from several common environments where the crop is cultivated. This study consisted of a genetic evaluation of 52 experimental grain sorghum hybrids and eight commercial cultivars. Hybrids were evaluated in 19 experiments representing the most varied cultivation conditions in Brazil. Traits of agronomic interest such as grain yield, flowering and plant height were analysed. Genotypic evaluation was performed following the REML/BLUP (Restricted Maximum Likelihood/Best Linear Unbiased Predictor) procedure; the MHPRVG (Harmonic Mean of Relative Performance of Genotypic Values) method was also employed to study stability and adaptability. Hybrids which stood out in terms of highest grain yield based on genotypic values, stability and adaptability were 0306037, 1G150, DKB 599, 0306039, 1G282 and 0307671. Of these, only 1G282 showed restrictions as to plant height. For flowering, experimental hybrids showed shorter cycles than commercial cultivars, confirming the efficiency of genetic improvement for this trait. With the analysis of grain yield considering days to flowering and plant height as covariates, it was observed that most of the hybrids of greater performance, showed grain yield to be positively influenced by plant height and days to flowering.